EDUCATIONAL LEADERSHIP AND MANAGEMENT: THEORY, POLICY, AND PRACTICE - BUSH, TONY; SARGSYAN, GOR (Main Issues Of Pedagogy And Psychology, 2020)
There is great interest in educational leadership in the early part of the 21st century because of the widespread belief that the quality of leadership makes a significant difference to school and student outcomes. There is also increasing recognition that schools require effective leaders and managers if they are to provide the best possible education for their learners. Schools need trained and committed teachers but they, in turn, need the leadership of highly effective principals and support from other senior and middle managers. While the need for effective leaders is widely acknowledged, there is much less certainty about which leadership behaviors are most likely to produce favourable outcomes. I examine the theoretical underpinnings for the field of educational leadership and management, assess different leadership models, and discuss the evidence of their relative effectiveness in developing successful schools.